eginning ASP.NET 2.0 E-Commerce in CSharp 2005 - Darie, Cristian (Apress, 2012)
Welcome to Beginning ASP.NET 2.0 E-Commerce in C# 2005: From Novice to Professional! The explosive growth of retail over the Internet is encouraging more small- to medium-sized businesses to consider the benefits of setting up e-commerce web sites. Although online retailing has great and obvious advantages, there are also many hidden pitfalls that may be encountered when developing a retail web site. This book provides you with a practical, step-by-step guide to setting up an e-commerce site. Guiding you through every aspect of the design and build process, this book will have you building high-quality, extendable e-commerce web sites quickly and easily.